Surgical Treatment of a Medial Clavicle Fracture Nonunion with Medial Clavicle Resection and Stabilization to the Sternum with Palmaris Longus Graft - M. O. Dion; S. Martel; S. Pelet (Case Reports in Orthopedics)
Medial end clavicular fractures are a rare occurrence. While most of these fractures can be appropriately managed with a nonoperative treatment, some cases of symptomatic nonunion might be surgically addressed to preserve sternoclavicular joint stability and ensure favorable outcomes. The open reduction and osteosynthesis procedure is a commonly performed procedure to treat clavicular fracture nonunion. However, few revision procedures have been described to address the occasional cases of hardware failure or recurrent nonunion of the medial end. In this report, the authors present a case of symptomatic nonunion of the medial clavicle initially treated with osteosynthesis. Implant failure with hardware migration was then treated by medial clavicle resection and stabilization to the sternum using a palmaris longus autograft and the figure-of-eight lacing technique. Excellent functional outcomes at three years of follow-up were obtained. To the authors’ knowledge, this is the first case reporting on a sternoclavicular stabilization with a tendon autograft for such an important bone deficit.